Balanced Scorecards: A Relational Contract Approach - Ola Kvaløy; Trond E. Olsen (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Reward systems based on balanced scorecards typically connect pay to an index, i.e. a weighted sum of multiple performance measures. We show that such an index contract may indeed be optimal if performance measures are non-verifiable so that the contracting parties must rely on self-enforcement. Under commonly invoked assumptions (including normally distributed measurements), the optimal self-enforcing (relational) contract between a principal and a multitasking agent is an index contract where the agent gets a bonus if a weighted sum of per-formance outcomes on the various tasks (the index) exceeds a hurdle. The weights reflect a trade-off between distortion and precision for the measures. The efficiency of the contract improves with higher precision of the index measure, since this strengthens incentives. Correlations between measurements may for this reason be beneficial. For a similar reason, the principal may also want to include verifiable performance measures in the relational index contract in order to improve incentives.
Keywords: 330; incentives; performance measures; relational contracts